2018
DOI: 10.12962/j2355262x.v17i2.a3894
|View full text |Cite
|
Sign up to set email alerts
|

Inhabitant’s Sense of Place in the Context of Tourism Kampung

Abstract: Kampung improvement program in Surabaya is considered successful in enhancing the quality of housing and settlement based on sustainable development. Recently, the kampungs development is directed toward tourism thematic (Thematic Tourism Kampung Programme) that adopts cultural conservation value. The goals are not only to improve the socioeconomic prosperity of Kampung's people, but also to conserve the kampung's culture and tradition. As a consequence, the function and meaning of kampung may change from urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 5 publications
0
13
0
3
Order By: Relevance
“…[33]. In the context of kampungs, a recent study showed that there are three aspects of sense of place, such as form (kampung layout, including building arrangement and orientation, form and building facade, street furniture, landmark); activity (social and domestic, behaviour setting patterns, social interaction); and meaning (place attachment and bonding with nature-family-social) [34]. To obtain the meaning of place, the third aspect of sense of place requires time or length of stay [35].…”
Section: Literature Review 21 Sense Of Placementioning
confidence: 99%
See 2 more Smart Citations
“…[33]. In the context of kampungs, a recent study showed that there are three aspects of sense of place, such as form (kampung layout, including building arrangement and orientation, form and building facade, street furniture, landmark); activity (social and domestic, behaviour setting patterns, social interaction); and meaning (place attachment and bonding with nature-family-social) [34]. To obtain the meaning of place, the third aspect of sense of place requires time or length of stay [35].…”
Section: Literature Review 21 Sense Of Placementioning
confidence: 99%
“…Moreover, the walking session time was only from 8:00 a.m. to 5:00 p.m. (weekdays and weekends), and the study did not consider the walking experiences during nighttime due to several considerations (e.g., time availability of the participants, dead town at night, less visibility, and safety). Second, this study only examined two aspects of the sense of place [34]: form and activity aspects. Third, recorded video data in this study was utilized to observe the participants' interactions with the place, which are not captured by the photographs.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kampung's public spaces can accommodate social interactions that have a direct influence on increasing people's sense of place (see table 1). From examples of those physical characters, it can be concluded that some aspects of form / physical attributes that affect the sense of place in kampung, especially tourism kampung are as seen in table 2 (Ramadhani, Faqih, & Hayati, 2018).…”
Section: Kampungmentioning
confidence: 99%
“…Through thematic kampung, the local potential and uniqueness characters such as social culture, architectural building, and local craft products could be explored and presented well for the tourists [7]. Therefore, these kind of kampung has two functions as a place to live for the community and a community-based tourism for commercialisation [8]. By encouraging public participation in developing thematic kampung, it does not only support the local community in improving their welfare but also strengthen the community.…”
Section: Introductionmentioning
confidence: 99%